MiR-30c-5p/ATG5 Axis Regulates the Progression of Parkinson’s Disease - Zhang, Li; Chen, Xiufen; Chang, Mingxiu; Jiao, Boning (Frontiers in Cellular Neuroscience, 2021)
Serum miR-30c-5p correlates with Parkinson’s disease (PD), yet its role has not been illustrated. This research analyzed the function of miR-30c-5p in the Parkinson’s disease. Behavioral evaluation was performed on MPTP-treated PD mice transfected with miR-30c-5p agomiR, antagomiR, siATG5, or 3-MA (an autophagy inhibitor). Oxidative stress-related factors, miR-30c-5p, and apoptosis- and autophagy-associated proteins in brain tissues or cells were determined by molecular experiments. Tyrosine hydroxylase (TH) and dopamine metabolic markers were detected using immunofluorescence and Diode Array Detector, respectively. Effects of miR-30c-5p and its target gene autophagy-related gene 5 protein (ATG5) on MPP+-treated SH-SY5Y cells were determined through a series of molecular experiments. MiR-30c-5p was upregulated but ATG5 was downregulated in PD mice. MiR-30c-5p antagomiR attenuated the decrease of ATG5 in PD mice. MiR-30c-5p antagomiR partly alleviated the behavioral symptoms and inhibited the increases of MDA, CAT and SOD in PD mice. The levels of Bcl-2, dopamine, dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), TH and LC3 II were downregulated in PD mice, while Bax, cleaved caspase-3, P62 and LC3 I were upregulated. However, miR-30c-5p antagomiR partly reversed the levels of these factors in PD mice. 3-MA could block the effects of miR-30c-5p antagomiR on PD mice. MiR-30c-5p antagomiR attenuated apoptosis and induced autophagy in brain tissues of MPTP-treated mice by targeting ATG5. In vitro assay results also showed that silence of ATG5 reduced the protective effect of miR-30c-5p downregulation on the cells. MiR-30c-5p regulates the progression of Parkinson’s disease through attenuating ATG5-inhibited apoptosis and –induced autophagy.